Exploring research trends and hotspots on PCSK9 inhibitor studies: a bibliometric and visual analysis spanning 2007 to 2023 - Lai, Ping; Xu, Shuquan; Liu, Ziyou; Ling, Jiayuan; Tian, Kejun; Yan, Jianwei; Chen, Dong; Zhong, Yiming; Xue, Jinhua (Frontiers in Cardiovascular Medicine, 2024)
BackgroundFollowing the identification of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors, research in this area has experienced significant growth. However, a thorough bibliometric analysis of this burgeoning field remains conspicuously absent. The current study aims to delineate research hotspots and anticipate future trends on PCSK9 inhibitors employing bibliometric analysis.MethodsA systematic search was conducted in the Web of Science Core Collection (WoSCC) to identify scholarly articles and reviews pertaining to PCSK9 inhibitors, yielding 1,812 documents. Data extraction was followed by analysis and visualization using Excel, VOSviewer, and CiteSpace software.ResultsA total of 1,812 publications were included in the final analysis. Ray, KK from the UK was the most prolific author, followed by Pordy, R from the USA. The USA led in publication output [number of publications (Np):776] and number of citations without self-citations (Nc) at 34,289, as well as an H-index of 93. “Cardiovascular System Cardiology” emerged as the predominant subject area. Amgen and the Journal of Clinical Lipidology were identified as the most active institution and journal, respectively. Keywords such as “lipoprotein(a),” “bempedoic acid,” “percutaneous coronary intervention,” “inclisiran,” “peripheral artery disease,” “mortality,” and “endothelial dysfunction” are gaining prominence in the field.ConclusionThe research on PCSK9 inhibitors is experiencing a sustained growth trajectory. The USA exerts considerable influence in this area, with the Journal of Clinical Lipidology expected to feature more groundbreaking studies. Research on “lipoprotein(a)”, “bempedoic acid”, “percutaneous coronary intervention”, “peripheral artery disease”, and “endothelial dysfunction” are poised to become focal points of future investigation.